G150(P) Forward thinking: seeking alternatives to bleeps. (25th October 2020) - Roberts, D; Webb, S; Newnham, AL
Abstract : Introduction: 'Bleep' systems are a central communication tool between medical and nursing teams in hospital. The majority of bleeps are for non-urgent tasks, this inefficient use of the bleep system leads to routine tasks take longer to complete and disruption of patient care. The Health and Social Care Secretary ordered pagers for non-emergency communications be removed from the NHS by 2021. Objective: Reduction in the number of bleeps for non-urgent tasks in a tertiary paediatric hospital. Methods: A multi-professional working group was established and developed a standard operating procedure (SOP) for bleeping including a 'traffic light' system with non-urgent tasks (completion within 1–4hrs) categorized as green. A job book with designated time slots for medical visits to each ward was introduced. A number of PDSAs (Plan, Do, Study, Act) cycles were completed using the job books but were ultimately unsuccessful. Therefore, a new direction using an electronic solution was explored. The FORWARD app (a secure messaging platform) was chosen to be piloted on two wards. Baton phones pre-installed with FORWARD were given to the medical and nursing teams alongside training. Communication via the platform was limited to non-urgent tasks and urgent tasks remained via the bleep system. Results: Telecommunications records from two weeks either side of implementation of FORWARD app demonstrated a significant reduction in the number of bleeps, the median decreasing from 21 to 12 (run chart available). The feedback was positive, and the nurses reported doctors responded more quickly on FORWARD. The main challenge was inconsistent wireless internet connection, affecting acknowledgment of tasks. Conclusion: This project has shown that a novel, secure messaging platform can effectively reduce the number of non-urgent bleeps. This requires an appropriate induction to the platform, a SOP on the use of the platform/bleeps and adequate IT infrastructure to ensure reliability and safety. This trial has also highlighted the importance of careful consideration of the governance implications when using patient identifiable data which is a clinical governance requirement for patient safety. Collaboration with the trust digital informatics and information governance team has led to the development of acceptable user policies to guide this.